2017
DOI: 10.1007/s10792-017-0635-y
|View full text |Cite
|
Sign up to set email alerts
|

Macular ganglion cell–inner plexiform layer thickness for detection of early retinal toxicity of hydroxychloroquine

Abstract: There was significant thinning of the macular GC-IPL in the absence of clinically evident HCQ-related retinopathy and VF abnormalities. Measurements of the macular GC-IPL thickness using SD-OCT may therefore be useful in the early diagnosis and in monitoring the progression of retinal changes in patients receiving long-term HCQ therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 26 publications
5
17
1
Order By: Relevance
“…However, in vitro studies suggested that the accumulation of HCQ was located in the outer retina or the choroidal tissue. Thus, our results might solve the previous discrepancies of some studies that found GCL thinning in HCQ retinopathy [11] and others that did not find any significant change in this layer [10]. On the other hand, our findings support that the first damaged retinal layer might be the ONL, as we discovered a significant thinning in patients with early HCQ retinopathy compared with control eyes in different retinal sectors, especially in the nasal area, as well as a significant correlation of ONL thickness and the duration of HCQ treatment.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…However, in vitro studies suggested that the accumulation of HCQ was located in the outer retina or the choroidal tissue. Thus, our results might solve the previous discrepancies of some studies that found GCL thinning in HCQ retinopathy [11] and others that did not find any significant change in this layer [10]. On the other hand, our findings support that the first damaged retinal layer might be the ONL, as we discovered a significant thinning in patients with early HCQ retinopathy compared with control eyes in different retinal sectors, especially in the nasal area, as well as a significant correlation of ONL thickness and the duration of HCQ treatment.…”
Section: Discussionsupporting
confidence: 74%
“…Retinal layer segmentation allows us to analyze the ganglion cell layer (GCL) together with the inner plexiform layer (IPL) with Cirrus OCT, which is referred to as GCIPL in the literature. Although the first results of this analysis showed no relationship between the thinning of GCIPL and HCQ retinopathy [10], recent results have led other researchers to hypothesize that GCIPL thinning could be an early indicator of it in screening use [11]. However, recent studies have located HCQ damage in the outer retina or the choroidal tissue, which is close to the findings of in vitro studies [12][13][14][15].…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…Finally yet importantly, structural retinal changes are not unique to preclinical or clinical AD. Similar changes may occur in other disease, such as hydroxychloroquine retinal toxicity [47] and glaucoma [48]. Exactly, we conducted the study according to rigorously exclusion criteria, which excluded individuals with retina-related disease, such as glaucoma, age-related macular degeneration, diabetic retinopathy and pathological myopia.…”
Section: Discussionmentioning
confidence: 99%